2015
DOI: 10.1038/onc.2015.81
|View full text |Cite|
|
Sign up to set email alerts
|

ATM-mediated KDM2A phosphorylation is required for the DNA damage repair

Abstract: The ataxia-telangiectasia mutated (ATM) protein is a key signaling molecule that modulates the DNA damage response. However, the exact mechanism by which ATM regulates DNA damage repair has not yet been elucidated. Here, we report that ATM regulates the DNA damage response by phosphorylating lysine-specific demethylase 2A (KDM2A), a histone demethylase that acts at sites of H3K36 dimethylation. ATM interacts with KDM2A, and their interaction significantly increases in response to DNA double-stranded, but not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 64 publications
1
65
0
Order By: Relevance
“…H3K36me2 is rapidly induced globally and locally after IR or etoposide treatment in a very rapid manner [47,76]. The increase of H3K36me2 at I-SceI-induced DSB site is mediated by recruiting Metnase (also SETMAR) and is required for NHEJ repair [47], which is in agreement with the role of Metnase in NHEJ [77,78].…”
Section: H3k36 Methylationsupporting
confidence: 69%
See 2 more Smart Citations
“…H3K36me2 is rapidly induced globally and locally after IR or etoposide treatment in a very rapid manner [47,76]. The increase of H3K36me2 at I-SceI-induced DSB site is mediated by recruiting Metnase (also SETMAR) and is required for NHEJ repair [47], which is in agreement with the role of Metnase in NHEJ [77,78].…”
Section: H3k36 Methylationsupporting
confidence: 69%
“…The recruitment of Metnase relies on phosphorylation of Ser495 by Chk1, but not by ATM [79]. We also found that dissociation of H3K36me2-specific demethylase JHDM1a/KDM2A with chromatin is also critical for this process, and this dissociation between KDM2A and chromatin is a result of ATM-dependent phosphorylation on Thr632 [76]. PHRF1 (PHD and ring finger domains 1) recognizes H3K36me2 via its PHD domain, meanwhile binds to NBS1 through the SDTE motif [80] (Fig.…”
Section: H3k36 Methylationmentioning
confidence: 80%
See 1 more Smart Citation
“…Histone was extracted as previously described (34). Briefly, cell pellets were lysed in hypotonic buffer, re-suspended in 0.4 N sulfuric acid and precipitated by trichloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of histone H3K36 dimethylation (H3K36me2) increase following DSBs as a result of either the dissociation of the histone demethylase KDM2A from chromatin or the catalytic activity of the histone methyltransferase Metnase, and recruit either the MRN complex or Ku70 family proteins to DSBs, respectively (18,19). Suv39h1-mediated histone H3K9 trimethylation (H3K9me3) at DSBs directly binds to and activates Tip60-a histone acetylase that is essential for ataxia-telangiectasia-mutated (ATM) activation (20,21).…”
mentioning
confidence: 99%